Natural-sunlight-driven synchronous degradation of 4-nitrphenol and rhodamine B over S-scheme heterojunction of α-Fe2O3 nanoparticles decorated CuBi2O4 rods. Issue 6 (December 2022) - Wang, Ji-Chao; Wang, Beibei; Shi, Weina; Qiao, Xiu; Yang, Xiaoxun; Zhang, Lifang; Zhang, Wanqing; Li, Renlong; Hou, Yuxia
Abstract: Enhancing photocatalytic efficiency of mixed-pollutant degradation is a critical issue for the application in wastewater purification, especially under natural-sunlight illumination. CuBi2 O4 rods decorated with Fe2 O3 nanoparticles were synthesized by the hydrothermal method. The Fe2 O3 /CuBi2 O4 composites exhibited significantly enhanced photocatalytic activity for Fenton oxidation of Rhodamine B (RhB) and 4-nitrophenol (4-NP) in the near-neutral catalytic system, and the degradation efficiency of the above two pollutants reached above 90% after 50 min of visible-light irradiation. Meanwhile, the good catalytic performance and stability were maintained in the seventh cycling test. Notably, the efficient synchronous degradation of the above mixed pollutants was accomplished under natural-sunlight over the optimal 7%Fe2 O3 /CuBi2 O4 catalyst. The staggered band structure in the heterojunction was determined by DRS and UPS results, and the S-scheme electron transfer mode was verified by the in situ-XPS measurement under dark and light conditions. The study is expected to be beneficial to explore step-scheme (S-scheme) semiconductor photocatalysts for natural-sunlight-driven Fenton oxidation of mixed pollutants. Graphical Abstract: ga1 Highlight: Fe2 O3 nanoparticles decorated CuBi2 O4 rods was synthesized. The photocatalysis for mixed degradation was accomplished under natural light. The 4-NP and RhB degradation performance was promoted by the heterojunction. S-scheme charge transfer was proven by the in situ-XPS measurement.